2007
DOI: 10.1074/jbc.m701448200
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Not Active Transport Underlies and Limits ERK1/2 Synapse-to-Nucleus Signaling in Hippocampal Neurons

Abstract: The propagation of signals from synapses and dendrites to the nucleus is crucial for long lasting adaptive changes in the nervous system. The ERK-MAPK pathway can link neuronal activity and cell surface receptor activation to the regulation of gene transcription, and it is often considered the principal mediator of synapse-to-nucleus communication in late-phase plasticity and learning. However, the mechanisms underlying ERK1/2 trafficking in dendrites and nuclear translocation in neurons remain to be determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 67 publications
1
44
0
Order By: Relevance
“…Interestingly, dynein knockdown did not significantly alter either CREB or NFAT reporter activity, although it has been reported that perturbations in the microtubule network could inhibit NFAT (32). While p53 is known to use dynein (26), the transport mechanisms of many nuclear localizing molecules are either unknown or are independent of the cytoskeleton (29,33,34). The further understanding of both dynein-dependent and independent mechanisms of NF-B transport may reveal additional regulatory points in this widespread signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, dynein knockdown did not significantly alter either CREB or NFAT reporter activity, although it has been reported that perturbations in the microtubule network could inhibit NFAT (32). While p53 is known to use dynein (26), the transport mechanisms of many nuclear localizing molecules are either unknown or are independent of the cytoskeleton (29,33,34). The further understanding of both dynein-dependent and independent mechanisms of NF-B transport may reveal additional regulatory points in this widespread signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…DNA transfection was performed after a culturing period of 8 days in vitro (DIV) using Lipofectamine 2000 (Invitrogen) as described previously (20). Infection of neuronal cultures with rAAVs delivering the different expression constructs was performed on DIV 3-6.…”
Section: Methodsmentioning
confidence: 99%
“…One of the intracellular signaling pathways activated by synaptic activity and a localized calcium signal in the immediate vicinity of synaptic NMDA receptors is the ERK-MAP kinase cascade (Bading and Greenberg, 1991;Grewal et al, 1999;Hardingham et al, 2001b;Sweatt, 2004;Wiegert et al, 2007). To investigate whether this signaling pathway is important for NMDA receptordependent regulation of nuclear geometry, we pharmacologically blocked this pathway using MAP kinase/ERK kinase (MEK) inhibitors PD98059 or UO126.…”
Section: Activity-induced Formation Of Nuclear Infoldings Requires Ermentioning
confidence: 99%